Concise syntheses of substituted indolizidine alkaloids via cyclization based on α-sulfinyl carbanions: preparation of (±)-indolizidines 167B and 209D, their epimers, and (±)-tashiromine - Manat Pohmakotr (2018)
(±)-Indolizidines 167B and 209D, their epimers and (±)-tashiromine have been successfully synthesized, starting from simple γ- or α-lactams. The strategy involves the cyclization of α-sulfinyl carbanion onto the carbonyl group of the lactam ring as the key step, leading to the indolizidines containing the phenylsulfinyl group, which are used as precursors for the preparation of the title compounds. © 2008 Elsevier Ltd. All rights reserved.